2017
DOI: 10.5455/ijlr.20170415115028
|View full text |Cite
|
Sign up to set email alerts
|

Fatty Acid Profiles and Physical Qualities of Different Varieties of Chicken and Duck Eggs

Abstract: The fatty acid profile and physical quality were assessed for the eggs of six varieties of chicken and duck viz. Desi, Kamrupa, Vanaraja, Pati, Nageswari, and Chara-Chemballi collected

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…According to this classification, Cherry Valley duck eggs with average weight of 94.23 g belongs to group of heavy duck eggs, while Pekin duck eggs with average weight of 71.91 g belongs to group of light duck eggs.According toHuang and Lin (2011), the average weight of duck eggs ranges from 60 to 90 g. Within that range were Pekin duck egg weights of 69.51 g(Balkan and Biricik, 2008), 77.57 g(Kralik et al, 2015), 80.7 g(Kokoszynski et al, 2007), 82.1-83.8 g(Onbasilar et al, 2007) and 82.8-86.7 g(Okruszek et al, 2008), but some authors recorded lower value like 59.03 g(Kavitha et al, 2017) or higher value like 91-45-95.56 g(Biesiada-Drzazga et al, 2014) 91.89 g (Al-Obaidi andAl-Shadeedi, 2016) and 97.31 g(Yuan et al, 2013). The weight of eggs from both duck breeds observed in this study was higher than eggs from some others duck breeds which were found in the literature: Pati duck of 57.83 g, Nageswari duck of 60.24 g and Chara-Chemballi duck of 66.23 g(Sarma et al, 2017), Dumyati duck of 61.42 g and Muscovy duck of 69.55 g(Ahmed, 2011), Mallard duck of 63.44 g (Al-Obaidi and Al-Shadeedi, 2016), Shan Ma duck of 67.30 g…”
supporting
confidence: 46%
“…According to this classification, Cherry Valley duck eggs with average weight of 94.23 g belongs to group of heavy duck eggs, while Pekin duck eggs with average weight of 71.91 g belongs to group of light duck eggs.According toHuang and Lin (2011), the average weight of duck eggs ranges from 60 to 90 g. Within that range were Pekin duck egg weights of 69.51 g(Balkan and Biricik, 2008), 77.57 g(Kralik et al, 2015), 80.7 g(Kokoszynski et al, 2007), 82.1-83.8 g(Onbasilar et al, 2007) and 82.8-86.7 g(Okruszek et al, 2008), but some authors recorded lower value like 59.03 g(Kavitha et al, 2017) or higher value like 91-45-95.56 g(Biesiada-Drzazga et al, 2014) 91.89 g (Al-Obaidi andAl-Shadeedi, 2016) and 97.31 g(Yuan et al, 2013). The weight of eggs from both duck breeds observed in this study was higher than eggs from some others duck breeds which were found in the literature: Pati duck of 57.83 g, Nageswari duck of 60.24 g and Chara-Chemballi duck of 66.23 g(Sarma et al, 2017), Dumyati duck of 61.42 g and Muscovy duck of 69.55 g(Ahmed, 2011), Mallard duck of 63.44 g (Al-Obaidi and Al-Shadeedi, 2016), Shan Ma duck of 67.30 g…”
supporting
confidence: 46%
“…In this study, the FAs of the egg albumen and yolk were composed mainly of MUFA (40.19%–44.34%), followed by SFA (30.66%–36.22%), and PUFA (2.29%–2.76%) ( Table 2 ). In the whole eggs of different varieties of Indian ducks, SFA, MUFA, and PUFA were found to be 45.49%–48.83%, 37.88%–45.00%, and 7.89%–10.57%, respectively [ 32 ]. Findings in Ismoyowati et al [ 33 ] showed that the egg yolk of Tegal ducks in the control group had MUFA, SFA, and PUFA contents of 43.86%, 27.43%, and 11.22%, respectively.…”
Section: Resultsmentioning
confidence: 99%